Lasertherapy as an adjuvante in the repair of Chemical lesions in the mouth (Research, Society and Development, 2021)
The objective of this paper is to report and discuss the case of a 38-year-old, black male patient, admitted to the Santa Casa de Campo Grande Beneficent Association, for a suicide attempt by ingesting caustic soda, causing numerous ulcers throughout the system. Gastrointestinal, especially the oral cavity presents with edema of great extension, friable and ulcerated mucous membranes, so for improvement and faster regeneration, photodynamic therapy and photobiomodulation therapy eith the use of low level laser was used. During hospitalization, the patient showed significant improvement in the healing of oral mucosa and tongue, showing a non-invasive from of treatment and with an axcellent therapeutic response.